2007
DOI: 10.1016/j.ijgo.2007.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic myomectomy for large intramural and submucous fibroids

Abstract: Hysteroscopic myomectomy is a therapeutic option for the treatment of submucous fibroids with uterine preservation [1]. However, transcervical resection of fibroids with deep intramural extension is performed only in selected patients [2]. A major concern is that complete hysteroscopic resection might result in uterine perforation or fluid overload.To avoid these problems, laparoscopic rather than hysteroscopic myomectomy was performed in 18 women who complained of persistent menorrhea probably due to submucou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, for patients who are not suitable for hysteroscopic surgery, laparoscopic myomectomy should be considered for surgeons with experienced surgical skills. Previous studies reported that for patients with type II submucous myomas in whom the size of the myoma was equal or greater than 40 mm, the surgeon should select the optimal surgical approach with discretion according to the patients’ conditions and its own technical level [ 26 , 27 ]. The aforementioned findings in this study suggest the advantage of laparoscopic myomectomy in the type II submucous myomas equal or greater than 40 mm.…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients who are not suitable for hysteroscopic surgery, laparoscopic myomectomy should be considered for surgeons with experienced surgical skills. Previous studies reported that for patients with type II submucous myomas in whom the size of the myoma was equal or greater than 40 mm, the surgeon should select the optimal surgical approach with discretion according to the patients’ conditions and its own technical level [ 26 , 27 ]. The aforementioned findings in this study suggest the advantage of laparoscopic myomectomy in the type II submucous myomas equal or greater than 40 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang et al [11] concluded that, in the presence of a submucous fibroid larger than 4 cm and with an intramural extension greater than 50%, laparoscopic rather than hysteroscopic myomectomy can be performed for the sake of safety and, if needed, for the concomitant removal of fibroids of a nonsubmucous type. However, this particular approach should be performed only by surgeons skilled in laparoscopic suturing.…”
Section: Discussionmentioning
confidence: 99%
“…Most of complications of HM are encountered with large sized myomas, or those with intramural extension (grade 1 or 2 according to the European Society of Hysteroscopy classification). They represent definite nightmare for hysteroscopists even with sufficient experience to the extent that some studies preferred laparoscopic approach in such cases (74). Hysteroscopically, several studies tried to facilitate one-step complete excision.…”
Section: Limitations Of Reconstructive Hmmentioning
confidence: 99%